An analysis of the concept of an ecological worldview - Czartoszewski, Jacek W. (Studia Ecologiae et Bioethicae, 2012)
The twenty-first century presents challenges for humanity in the context of massive environmental contamination. This problem can only be solved through awareness of man’s place in the world of the Absolute. This requires a high level of self-awareness. This brings about the need for a new approach to socially-oriented ecological thinking; host axiology that values ecology. This worldview without ideology and inaccuracy should be supported by a real basis of Aristotelian-Thomistic thinking. Furthermore, it must avoid gaps in knowledge, hence the community, in addition to possessing scientific, technical, legal and economic knowledge, should be knowledgeable of humanistic anthropology, axiology, theodicy, and religion, gained comprehensively through the use of common sense knowledge, wisdom, science, philosophy, and religion. Otherwise, gaps, inconsistencies, and even contradictions within the meaning of the world dominate and lead to quarrels and antagonism.